Analysis of the competitive load in u16 handballers as a function of the final result - David Mancha Triguero; María Reina; Belén Baquero; Javier García-Rubio; Sergio J. Ibáñez (Federación Extremeña de Balonmano; University of Extremadura, 2018)
The current trends in team sports training are based on the reproduction of the specific performance of the game in a non-competitive context. A study of the characteristics of the competition is required to gather the information necessary to design and plan the training. Due to the lack of knowledge of the quantification of the competitive load in training categories, the objective of this work is to characterize the internal and external load demands of the competition and to know if these demands are directly related to the final result in this category. The study was carried out in 19 sub 16 subjects who played the final of a regional competition. Four internal load and three external load variables were analyzed. A Wimü model inertial devices were used from RealTrack System. A TEST T was made for samples related to the purpose of making a comparison of the variables depending on the team. The results obtained by both teams are very similar, there is HeartRate Max the only significative variable. The result of the game is not a predictor of the physical performance of the team.